Perseweracja motywów w poezji Jerzego Ficowskiego - Świerczewska, Beata (Annales Universitatis Paedagogicae Cracoviensis | Studia Historicolitteraria, 2016)
Perseveration of motifs in Jerzy Ficowski’s poetry Reading Ficowski’s poems requires researchers of his work to be erudites, thanks to which it is easier for them to move smoothly through the meanders of tradition and culture but also of everyday life presented in Ficowski’s image of the world. The image itself consists of the recurring (in every poetry volume) motifs and depictions. While reading Ficowski’s poems it is difficult not to notice this repetitiveness - sometimes exact and detailed, sometimes modified. An attempt to systematize a phenomenon such as perseveration of motifs in Ficowski’s poems led me to identifying the following thematic areas: memory and attitude towards the past, glorification of everyday life and elements belonging to it, proverbs and sayings as elements of folklore occurring in this poetry. In this article, through the analysis of Ficowski’s poems a phenomenon of perseveration of motifs used by a poet to create his own image of the world was shown. Key words: perseveration; past; memory; everyday life; proverbs; myth; folklore;